Health promotion of long-haul truck drivers and their families - Fernanda Lise; Eda Schwartz (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to describe the development of a Health Information and Communication Technology for the health care of long-haul truck drivers and their families. Methods: this is a description of the development of an Information and Communication Technology, developed from March to September 2023, following the systematization of the experience in five steps: 1) starting point, 2) initial questions, 3) recovery of the lived process, 4) background reflection, and 5) arrival points. Results: the technology called "Work-Family Balance," electronically available, presents resources for the health care of long-haul truck drivers. It is anchored in studies on the health of long-haul truck drivers, notes from the International Labor Organization, the Strategic Action Plan for Confronting Chronic Diseases and Non-Communicable Diseases in Brazil, 2021-2030, and the Declaration by the International Association of Family Nursing. Final Considerations: the theoretical improvement of nursing can potentially improve the health care of long-haul truck drivers, prevent Chronic Non-Communicable Diseases, and promote work-life balance to achieve the goals of Agenda 2030.